2011
DOI: 10.1007/s12070-011-0251-5
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural Hearing Loss in Patients with Chronic Suppurative Otitis Media

Abstract: Even though there are other complications of chronic suppurative otitis media, the aspect of hearing loss is often studied. Nevertheless, the occurrence of sensorineural hearing loss in patients with this disease is still controversial. This study aim (1) to assess the association between sensorineural hearing loss and chronic suppurative otitis media, (2) to investigate some clinical factors that might affect the sensorineural component in patients with this disease. This was a retrospective analysis of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 17 publications
8
46
1
3
Order By: Relevance
“…Still, many of our children had mixed hearing losses and were left with educationally significant elevations in their bone lines after tympanoplasty. Similar results have been reported in Nigerian patients (39 dB mean SNHL) but not in Italian patients (3 dB mean SNHL) with chronic suppurative otitis media. There are several possible explanations for these sensorineural losses.…”
Section: Discussionsupporting
confidence: 89%
“…Still, many of our children had mixed hearing losses and were left with educationally significant elevations in their bone lines after tympanoplasty. Similar results have been reported in Nigerian patients (39 dB mean SNHL) but not in Italian patients (3 dB mean SNHL) with chronic suppurative otitis media. There are several possible explanations for these sensorineural losses.…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies have demonstrated that CSOM is able to cause SNHL in addition to CHL (Papp et al, 2003;da Costa et al, 2009;Kolo et al, 2012;Yang et al, 2014). Infection of the middle ear leads to the generation of inflammatory mediators such as nitric oxide and arachidonic acid metabolites (Table 3), which can cause functional as well as morphological changes in the auditory structures (Housley et al, 1988;Jung et al, 1992;Guo et al, 1994;Clerici et al, 1995;Jung et al, 2003).…”
Section: Hearing Lossmentioning
confidence: 99%
“…These bacterial toxins can be exotoxins (proteins) produced by both Gram-positive and Gramnegative bacteria, or endotoxins (LPSs of the outer membrane of Gram-negative bacteria). These infection-associated toxins might cause direct damage to hair cells, especially those at the cochlear base where the hair cells are sensitive to high-frequency sounds (Kolo et al, 2012). A significant loss of outer and inner hair cells, as well as significant atrophy of the stria vascularis in the basal turn of the cochlea, has been observed in CSOM patients.…”
Section: Hearing Lossmentioning
confidence: 99%
“…The perforation of TM is because of chronic suppurative otitis media (CSOM) in a majority of outpatient cases while trauma accounts for only limited number of them. [1] Bilateral TM perforation is more common as a result of CSOM. Myringoplasty is a simple closure of TM indicated especially when healing does not occur after conservative measures.…”
Section: Introductionmentioning
confidence: 99%